Enculturated Education for Strengthening Character Education in Preventing Intolerance and Radicalism - Cardinale, Pamela; Rofi’i, Muhammad Syaroni; Samputra, Palupi Lindiasari; Achdiawan, Ramadhani (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractIntolerance and extremism have recently increased in the academic atmosphere or among students. The purpose of this study was to discover the origins of intolerance and radicalism among students, identify the core cause of educational problems, and examine the role of cultural education in building the character of Indonesian students. The Delphi approach was used to assess data gathered from a variety of expert informants. The study's findings revealed four significant causes of intolerance and radicalization: personal factors, education, economic-social-political-cultural issues, and a lack of religious comprehension. The study also found that religious education is less in-depth, with less reading, weak persuasive logic, and a focus on binary truth. Cultural education begins with establishing superior national identity through the Pancasila character ("gotong-royong" or cooperation, empathy, and good critical-thinking abilities); fosters the habit of reading texts critically and comprehensively. Both serve as the foundation for pupils' capacity to solve complex challenges. This study makes recommendations for promoting pupils' religious belief in God and tolerance values. Intoleransi dan ekstremisme akhir-akhir ini meningkat di lingkungan akademik atau di kalangan mahasiswa. Tujuan dari penelitian ini adalah untuk mengetahui asal mula intoleransi dan radikalisme di kalangan siswa, mengidentifikasi inti penyebab masalah pendidikan, dan mengkaji peran pendidikan budaya dalam membangun karakter siswa Indonesia. Pendekatan Delphi digunakan untuk menilai data yang dikumpulkan dari berbagai informan ahli. Temuan penelitian mengungkapkan empat penyebab signifikan intoleransi dan radikalisasi: faktor pribadi, pendidikan, masalah ekonomi-sosial-politik-budaya, dan kurangnya pemahaman agama. Studi tersebut juga menemukan bahwa pendidikan agama kurang mendalam, dengan bacaan yang kurang, logika persuasif yang lemah, dan fokus pada kebenaran biner. Pendidikan budaya diawali dengan pembentukan jati diri bangsa yang unggul melalui karakter Pancasila (“gotong-royong” atau kerjasama, empati, dan kemampuan berpikir kritis yang baik); menumbuhkan kebiasaan membaca teks secara kritis dan komprehensif. Keduanya berfungsi sebagai dasar bagi kapasitas siswa untuk memecahkan tantangan yang kompleks. Kajian ini memberikan rekomendasi untuk mempromosikan keyakinan agama siswa kepada Tuhan dan nilai-nilai toleransi.How to Cite: Cardinale, P., Rofi’I, M. S., Samputra, P. L., Achdiawan,  R. (2021). Enculturated Education for Strengthening Character Education in Preventing Intolerance and Radicalism. TARBIYA: Journal of Education in Muslim Society, 8(1), 20-43. doi:10.15408/tjems.v8i1.20359.